TALENT DEVELOPMENT AND EDUCATION IN TOURISM - Unković, Slobodan (The European Journal of Applied Economics, 2017)
Tourism, both international and domestic, has become one of the most important factors of social and economic development throughout the world. For that reason, quality of education in the field of tourism and strategies for talent development should be considered matters of utmost importance. In this paper, I present my views on primary, secondary and higher education in the field of tourism, as well as on education of tourist guides. I also present a brief case study of Singidunum University, as an example of good practice in higher education in the field of tourism.